World's alternative energy and national perspectives - Пабат, А. А. (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2015)
In the article the current state and prospects of using the inexhaustible and renewable sources of energy (NRSE) in the world, their general and technical capacity, scope, advantages and disadvantages compared to fossil fuels are studied. Particular attention is paid to non-traditional renewable energy. The prospects of Ukraine to learn and use these sources are analised.